Tepubina bandar: Isu dan kaitannya dengan kesihatan ekosistem lembangan saliran - Noorazuan Md Hashim,; Asmala Hj Ahmad, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2007)
Investigating urban imperviousness impact, in particular, the effects of urban imperviousness on ecosystem health has become an important agenda in catchment hydrological studies, both in developed and developing countries. This article highlights global and local issues related to imperviousness, its research methodological development and its potential use as an ecosystem health indicator for catchment areas in Malaysia. Examination of the Langat Stesen Bt 11 sub-basin has proven the heightened effect of urban imperviousness on the river water quality. The acceleration of this urban imperviousness as an indicator of rapid physical development of the study area which began in 1988 has contributed to increased suspended solids (SS) in the river water. Accelerated urbanisation and population growth may be correlated to increases in domestic wastes and sewage which had led to dramatic readings of parameters such as COD, BOD and Ammonical-Nitrogen indicating serious pollution. The paper concludes that at least imperviousness standards as suggested by the Schueler model (1994) may be relied upon in planning the drainage systems of new towns so that environmental problems such as water pollution and flash floods may be averted